Pengembangan Komik Sains Cacing Nyale Sebagai Media Pembelajaran Pendukung Materi Biologi di Sekolah Menengah Pertama - Handayani, Baiq Sri; Bachtiar, Imam; Japa, Lalu; Bahri, Syamsul; Sukma, Izza Melati (Postgraduate, University of Mataram, 2024)
Media that discusses Nyale worm material in detail and clearly has never been developed before. This research aims to develop Nyale worm science comics as supporting media for biology learning in schools. The type of research used is research and development (R&D) using the Plomp model which consists of 5 stages. However, this research was only carried out up to stage 4, namely preliminary investigation, design, realization/construction, as well as tests, evaluation and revision. The subjects of this research were MTs Nurul Jannah students for the 2022/2023 academic year, totaling 35 students. The data collection technique uses a questionnaire sheet to obtain validity data and student responses. The data obtained was then analyzed descriptively. The research results show that science comics and nyale worms received an average of 83.93% based on material experts, 91.20% based on media experts with a very decent category. Based on user responses, the Nyale Worms comic received a score of 71.92% in the decent category. This research concludes that the Nyale worm science comic is suitable for use in the learning process to increase students' interest in learning.